Philosophical Insights into the ‘great’ of Great River Culture through Chuang-tzu’s ‘Autumn Floods’ - Renzhong Cui (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Great River Culture, deeply embedded in the fabric of Chinese history, symbolizes the enduring legacy of the Yellow River and its influence on the cultural and spiritual development of the Chinese nation. Understanding the concept of ‘great’ within this cultural context is vital for appreciating its profound impact. In Chuang-tzu’s ‘Autumn Floods,’ the exploration of the relative nature of ‘small’ and ‘great’ provides an invaluable perspective for this understanding. This paper uses the method of literature analysis to delve into the philosophical content expressed by Chuang-tzu in the seven questions and answers between the Deity of the Yellow River and the Deity of the Northern Sea. Chuang-tzu elucidates that understanding the ‘small’ is necessary to discuss the great, the distinction between ‘small’ and ‘great’ is not constant, and the separation between the Dao and objects, along with the concept of reverting to the true essence. Hence, the ‘small’ and the ‘great’ are interdependent, with no fixed division between them. Discussing the ‘great’ only in the tangible and limited sense of ‘seeing things as objects’ is far from sufficient. The higher level of the intangible and infinite Dao represents the true essence of the concept of ‘great’ in river culture.